PENCANTUMAN SERTIFIKAT KEANDALAN (LOGO TRUSTMARK) SEBAGAI BENTUK PERLINDUNGAN KONSUMEN E-COMMERCE DITINJAU DARI PERATURAN YANG BERLAKU - Nathania Tesalonica; Bernadetta Tjandra Wulandari (Faculty of Law, Maranatha Christian University, 2021)
The development of information and communication technology that is increasing has made a major contribution to meeting human needs. The presence of the internet provides convenience in making buying and selling transactions, through e-commerce. The presence of Law no. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions is one of the legal instruments in protecting e-commerce consumers. The law regulates one form of protection that can be carried out through the inclusion of a certificate of reliability (trustmark). Based on the analysis using the normative juridical research method, it was found that in the case of the inclusion of a reliability certificate (trustmark) issued by a Foreign Reliability Certification Agency, the government has not taken legal action regarding this matter, so that the inclusion of a reliability certificate (trustmark) can still be applied as long as there are no regulations issued. Arrange. In relation to legal actions that can be taken by the parties for losses in e-commerce transactions due to the absence of a trustmark logo, namely by imposing sanctions on business actors and consumers can demand rights that should be fulfilled in buying and selling transactions through existing mechanisms.